CONVERGENCE OF MARRIAGE BETWEEN ISLAMIC LAW AND CUSTOMARY LAW - Elfirda Ade Putri; Ahmad Baihaki; Windy Sri Wahyuni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Customary law is a collection of norms and rules derived from the habits or customs of the community, both written and unwritten. Marriage is a physical and mental bond between a man and a woman with the aim of building a family that is sakīnah, mawaddah, rahmah and barakah. The provisions of customary law and Islamic law have significant differences. Marriage in Islamic law regarding joint property and mutual inheritance between adopted children and adopted parents can be done through the institution of mandatory wills. These two legal provisions adopted from customary law are the result of the ijtihad of Indonesian scholars, because the second issue is not found in fiqh. This innovative creation of Indonesian scholars, apart from being a manifestation of the dynamic and creative characteristics of Islamic law, is also the identity of Islam Nusantara in the field of law. Seen from this aspect, the Indonesian KHI, in the language of the Law, can be referred to as Indonesian Jurisprudence because in addition to having an Indonesian personality, it also adopts customary law that lives in local traditions.